2019
DOI: 10.1159/000506770
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Lately Diagnosed Cerebrotendinous Xanthomatosis

Abstract: Objectives: Cerebrotendinous xanthomatosis (CTX) is a rare autosomal recessive inborn lipid storage disorder due to various pathogenic mutations in the CYP27A1 gene. Although the symptoms begin commonly in infancy, CTX diagnosis is often delayed. In this study, we report 7 Turkish CTX patients who had a delayed diagnosis despite early clinical signs and belonged to 6 unrelated families. Methods:We have retrospectively evaluated clinical, laboratory, imaging, and genetic findings of CTX patients, which were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Early recognition of CTX as a syndrome is important because supplementation with chenodeoxycholic acid may alleviate, and in some cases resolve GI symptoms and stabilize neurologic symptoms. 79,80,81…”
Section: Cerebrotendinous Xanthomatosismentioning
confidence: 99%
See 1 more Smart Citation
“…Early recognition of CTX as a syndrome is important because supplementation with chenodeoxycholic acid may alleviate, and in some cases resolve GI symptoms and stabilize neurologic symptoms. 79,80,81…”
Section: Cerebrotendinous Xanthomatosismentioning
confidence: 99%
“…Despite impaired bile acid synthesis, there is no evidence that fat absorption is impaired in CTX 79 and therefore some have suggested that bile alcohols present in the gut lumen may interfere with gut motility or lead to electrolyte/ fluid disequilibrium or bacterial dysbiosis. Early recognition of CTX as a syndrome is important because supplementation with chenodeoxycholic acid may alleviate, and in some cases resolve GI symptoms and stabilize neurologic symptoms 79,80,81 …”
Section: Primary Movement Disorders With Associated Gi Symptomsmentioning
confidence: 99%
“…During the systematic review, 568 cases of CTX patients were identified. 5,6,8,9,11,13, In this cohort, 392 cases were genetically confirmed, with 114 different CYP27A1 pathogenic variants. We also distinguished between a cohort of patients of Asian and non-Asian origin in order to highlight any differences between them.…”
Section: Polish Cohort and Reviewed Casesmentioning
confidence: 99%
“…28 Moreover, in various studies, we found that patients with cerebellum changes detected in MRI as a part of cognitive impairment presented with dysthymia, depression, behavioral changes, irritability, emotional lability, and anxiety. 13,21,22,28 However, such psychiatric and cognitive manifestations were also present in cases without evident cerebellar involvement. 28 Ultimately, in some cases, developmental defects of the nervous system could have a decisive influence on cognitive functions.…”
Section: Cognitive Impairment and Psychiatric Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation